KUALITAS SEMEN CAIR SAPI LIMOUSIN SELAMA PENDINGINAN MENGGUNAKAN PENGENCER CEP-2 DENGAN PENAMBAHAN BERBAGAI KONSENTRASI SARI KEDELAI - Nanang Sugiarto; Trinil Susilawati; Sri Wahyuningsih (TERNAK TROPIKA Journal of Tropical Animal Production, 2014)
Egg yolk is most commonly used in semen extender for preservation and cryopreservation but potential risk of xenobiotic contamination has raised question upon the use of egg yolk. Therefore, the present study was designed to evaluate soy milk CEP-2 based extender on liquid semen of Limousin during chilled preservation. Semen divided into five groups and diluted at 1/8 (semen/extender) with 7,5%, 10%, 12,5%, 15% soy milk respectively (CEP-2+7,5% SK, CEP-2+10% SK, CEP-2+12,5% SK, CEP-2+15% SK) and 10% egg yolk (CEP-2+10% KT). The results of current study showed egg yolk give the superior effect on maintaining sperm quality (motility, viability and abnormality) after 24 hours in chilled preservation. The motility and viability in CEP-2+Soy Milk groups were significantly (P<0,01) lower compared to CEP-2+10% KT extender, but there is no difference (P>0,05) on motility percentage between CEP-2+15% SK and CEP-2+10% KT. Furthermore, the abnormality in CEP-2+10% KT was significantly lower than those CEP-2+Soy Milk groups (P<0,01). Total motile sperm count was significantly higher (P<0,01) in all treatments compared to the standard criteria of SNI 40 million cells/mL. Using soy milk in CEP-2 (Cauda Epididymal Plasma) extender can’t produce the comparable value on maintaining sperm quality compared to the use of egg yolk as extracellular cryoprotectant during chilled preservation, but CEP-2+15% SK (Soy Milk 15%) had shown decent capability on maintaining sperm motility and total motile sperm count.   Key Words : CEP-2, soy milk, egg yolk, liquid semen, chilled preservation